Comparing pain relief and functional improvement between methylprednisolone and dexamethasone lumbosacral transforaminal epidural steroid injections: a self-controlled study - Donohue, Nicholas K.; Tarima, Sergey S.; Durand, Matthew J.; Wu, Hong (The Korean journal of pain, 2020)
Previous studies have shown varying results between lumbosacral transforaminal epidural steroid injections (TFESIs) performed with particulate versus non-particulate corticosteroids. The purpose of this study was to investigate the difference in pain relief and functional improvement between particulate and non-particulate lumbosacral TFESIs in patients who had undergone both injections, sequentially. This was a self-controlled, retrospective study of 20 patients who underwent both a methylprednisolone and a dexamethasone TFESI to the same vertebral level and side. Primary outcomes included pain relief according to the visual analogue scale (VAS) and functional improvement determined by a yes/no answer to questions regarding mobility and the activities of daily living. Post-injection data was recorded at 2, 3, and 6 months. A decrease in VAS scores of -3.4 ± 3.0 (mean ± standard deviation), -3.1 ± 3.1, and -2.8 ± 3.4 was seen for the methylprednisolone group at 2, 3, and 6 months, respectively. Similar decreases of -3.9 ± 3.5, -3.4 ± 2.8, and -2.3 ± 3.4 were seen in the dexamethasone group. There was no significant difference in pain relief at any point between the two medications. The percentage of subjects who reported improved function at 2, 3, and 6 months was 65%, 51%, and 41%, respectively, for the methylprednisolone group and 75%, 53%, and 42% for the dexamethasone group. These findings support the use of non-particulate corticosteroids for lumbosacral TFESIs in the context of documented safety concerns with particulate corticosteroids.